Time Management Strategies of Triple-Role: The Case Study of Female Students of Islamic Higher Education - Ahmad Yani; Suharno Pawirosumarto; Muhammad Ridwan (Ta'dib, 2026)
This article aims to reveal the time management practices of female students at the State Islamic University who have three roles: first, as students with academic responsibilities on campus; second, as workers or career women; and third, as wives to their husbands and mothers to their children, with the obligation to take care of various household matters. This article uses a qualitative research method with four female students who have these three roles as research subjects. There are two sources of data in this study, namely primary data (interview and observation results) and secondary data (library data from scientific articles, books, etc.). The data collection methods used were observation and interviews. Meanwhile, the data analysis technique used is the technique popularised by Miles et al., which consists of data condensation, data presentation, and conclusion drawing. The findings of this study indicate that not all female students who have three roles have good study time management. This means that these female students have difficulty managing their time, which has an impact on their academic achievement. However, female students who have good time management and are able to develop discipline and have planned and organised learning strategies can improve their academic achievement. In fact, they successfully completed their final studies well and in accordance with the set targets. This study has implications for female students, especially in terms of good time management, by designing, managing, and adapting to various things, so that female students can discipline themselves.